Adam canfield of the dash - Winerip, Michael (Walker London, 2005)
Adam Canfield of The Slash is a middle-grade novel by Catherine Jinks that follows the adventures of Adam Canfield, a resourceful and determined young journalist. Set in a small town, Adam navigates the challenges of school life while pursuing his passion for writing. He collaborates with his friends to uncover stories and expose injustices in their community, often leading to humorous and enlightening situations. The book explores themes of friendship, courage, and the importance of standing up for what is right, making it a relatable and inspiring read for young audiences.